Kemampuan Dosen dalam Membuat Soal HOTS Pada Pembelajaran Abad 21 - Ahmad Ali; Wiwin Pramita Arif; Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Rahmawati Darussyamsu; Dasmo Dasmo; Nurfadhilah Nurfadhilah; Nur Fadli Hazhar Fachrial (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Twenty-first century learning requires high-level thinking skills including critical thinking, communication, collaboration, and creativity known as the 4Cs. The purpose of this study was to determine the ability of the lecturers of the Biology Education Study Program at UIN Alauddin Makassar in making Higher Order Thinking Skills (HOTS) questions and to find out the responses of the lecturers of the Biology Education Study Program at UIN Alauddin Makassar on the importance of developing HOTS questions. This research is a quantitative descriptive research. This research was carried out in the odd semester of the 2019/2020 Academic Year with the research subjects of all lecturers of the Biology Education Study Program at UIN Alauddin Makassar who have educational backgrounds according to the study program as many as 12 people. Data collection techniques through question documentation and questionnaires. Data were analyzed by descriptive statistics. The results showed that Lecturers of the Biology Education Study Program were able to make higher order thinking questions (HOTS) with a percentage of 33% Very Able, 8% Able, and 17% Enough, while the remaining 42% with the criteria of Poor. As many as 85% of the Lecturers of the Biology Education Study Program at UIN Alauddin Makassar gave a positive response to 74% of items stating the importance of making higher order thinking questions (HOTS). Suggestions from this study was that Biology Education lecturers can innovate HOTS-based educational evaluations.